The Community Assistance in Zakat Management Using an Intelligent Web-Based Application for Mustahik Mapping in Kuantan Singingi Regency - Roni Putra; Ishadi Ishadi; Lidus Yardi; Elpianto Elpianto (CV. AFDIFAL MAJU BERKAH, 2026)
This community service program aimed to strengthen the effectiveness, transparency, and accountability of zakat management through the implementation of an intelligent web-based application for mustahik mapping in Kuantan Singingi Regency. The program employed an educational and participatory approach involving mustahik, zakat administrators, and zakat management practitioners. Activities were conducted through interactive assistance, application demonstrations, Focus Group Discussions (FGDs), and evaluation sessions. Data were collected through observation, discussion documentation, and semi-structured interviews, and analyzed using qualitative descriptive analysis. The results indicate that the application improved the accuracy of mustahik data management, reduced duplication and misclassification, and accelerated data retrieval and decision-making processes. FGDs played a critical role in strengthening stakeholder participation, fostering collective problem-solving, and enhancing a sense of ownership toward the system. Participants demonstrated improved understanding of digital zakat management, increased confidence in using technology-based systems, and greater readiness to adopt data-driven practices. Overall, the program concludes that intelligent web-based applications, when supported by participatory implementation and capacity-building activities, have strong potential to improve the quality, fairness, and sustainability of zakat management at the local level.